Synthetic Studies on the Bis-Anthraquinoid Core of the Angelimicins - Li, Jialiang; Mootoo, David R. (Synthesis, 2013)
Bidirectional Hauser and Michael–Dieckmann annulation strategies for the preparation of bis-anthraquinoid framework of the angelimicin family of natural products are explored, using cyclohex-2-enone and biphenyl Michael donors, which are prepared from 1,2,5-trimethoxy-3-methylbenzene. The Hauser annulations are not productive, but the Michael–Dieckmann reactions proceed in 40% yield. Attempts to aromatize these biphenyl cycloadducts proved unsuccessful. This result differs from the success reported in another study of the same reaction. In contrast, aromatization of the related monomeric Michael–Dieckmann cycloadduct proceeds smoothly.
Keywords: biaryl; annulation; Michael–Dieckmann; aromatization; angelimicins